2016
DOI: 10.1093/ehjci/jew173
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of inflammatory biomarkers and carotid artery disease in prediction of significant coronary artery disease as assessed by coronary computed tomography angiography

Abstract: Among asymptomatic intermediate-risk patients, the presence of increased IL6 levels in addition to traditional risk factors (male gender with diabetes) and carotid artery disease predicts higher rates of obstructive CAD and it could be of help to identify which subset of asymptomatic patients could be referred to CCTA for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…The unique ability of CCTA to identify adverse plaque features such as low‐density noncalcified plaque and positive remodeling of the vessel is of great clinical value . Despite the power of coronary stenosis information in predicting event occurrence and correctly reclassifying most patients, the present analysis shows that the characterization of plaque and, specifically, the presence of positive remodeling, are able to further improve risk stratification, particularly lowering the risk of patients who do not show this feature.…”
Section: Discussionmentioning
confidence: 74%
“…The unique ability of CCTA to identify adverse plaque features such as low‐density noncalcified plaque and positive remodeling of the vessel is of great clinical value . Despite the power of coronary stenosis information in predicting event occurrence and correctly reclassifying most patients, the present analysis shows that the characterization of plaque and, specifically, the presence of positive remodeling, are able to further improve risk stratification, particularly lowering the risk of patients who do not show this feature.…”
Section: Discussionmentioning
confidence: 74%
“…Subjects were younger than our population, nearly 50% of them were women, and cardiovascular risk factors prevalence was different with more hypertension and dyslipidemia and less diabetes mellitus and smoking habit. Finally, just as Cohen's study and ours, they considered the number of affected vessels and not angiographic scoring systems . Studies performed with invasive coronary angiography found a relationship between CAD extension, defined by the number of affected vessels or by angiographic scoring systems, and carotid disease, mostly CIMT, in patients suffering stable angina and/or acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 77%
“…Carotid disease, defined as carotid intima‐media thickness (CIMT) and/or the presence of plaques, has been associated in epidemiological studies with myocardial infarction, stroke, and death, and its study improves the ability of risk functions to predict cardiovascular events . It has also showed its utility for coronary artery disease (CAD) diagnosis in patients with ischemic heart disease suspicion scheduled for invasive and noninvasive diagnostic testing . In that sense, American and European guidelines on the management of stable CAD agree that a history of cerebrovascular or peripheral artery disease increases the likelihood of CAD and ultrasound assessment of the carotid arteries in patients with suspected CAD without known atherosclerotic disease is a grade IIa level C recommendation for diagnosis and preventive purposes in the European guidelines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by a renewed awareness of this issue the matter, the researchers have been now reanalysing old data and developing conceiving focused prospective studies based on modern and thrilling technology such as computed tomography angiography (CTA) and cardiac magnetic resonance (CMR). In the light of the dramatic technological advances, CTA and CMR have been giving the possibility offer the ability to characterize both the coronary artery disease (CAD) and the myocardium to at a very high level of detail [4][5][6]. This could allow the imaging modality armamentarium to differentiate the pathophysiology of the IHD and other major heart diseases within each gender.…”
Section: Introductionmentioning
confidence: 99%